The effect of age, educational level, gender and cognitive reserve on visuospatial working memory performance across adult life span. Issue 2 (3rd March 2020) - Zarantonello, Lisa; Schiff, Sami; Amodio, Piero; Bisiacchi, Patrizia
ABSTRACT: Working memory (WM) is a limited capacity cognitive system that temporarily holds information for processing. In the present study, we tested the effect of age, gender and cognitive reserve in terms of educational level, working and leisure time activities on an active visuospatial WM task. One-hundred thirty-four participants between 20 and 80 years old performed an n-back task with different degree of WM demanding. Reaction times (RTs) became slower and accuracy decreased with age; the former started to decline in participants that were 35 years old, the latter in participants that were 57 years old. Males were faster than females. Educational level (10 years in accuracy and 15 years in RTs) showed a positive effect on accuracy and RTs. Cognitive reserve had a positive effect on accuracy but no effect on RTs. In conclusion, age-related decline influenced earlier the speed and later the accuracy in a task that required active processes. While male was faster independently of WM demanding and age, middle school degree and an average cognitive reserve prevent errors during performance. Coherently, high school degree prevents slowing down but only in low demanding condition.